Psycometric Properties of Employee Retirement Readiness Scale - Grace Angela; Fajrianthi Fajrianthi; Dewi Syarifah; Inastuti Rahmadhani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Retirement is considered a worrying time, especially for those who are not mentally prepared. This study aims to develop a retirement preparation scale based on a psychometric approach. The survey design used a correlation approach with the survey data collection technique. The respondents are the employees at PT. Pembangkitan Jawa Bali (PJB) (N = 57). The retirement scale developed includes five dimensions: Physical, mental, financial, performance, and health assessment. To test the internal structure of the scale, a content validity test was conducted using Aiken V and Confirmatory Factor Analysis. The results show that the measuring tool for retirement readiness fits the existing data in the field. To measure the retirement readiness of employees at PT PJB, 17 items consisting of two open-ended questions and 15 Likert scale items can be applied. The results also indicate that the measurement tool for employee retirement readiness of PT. PJB is valid and reliable to be applied within the scope of PJB's subsidiaries.